A INTERDISCIPLINARIDADE NA CONSTRUÇÃO DOS PROJETOS POLÍTICO-PEDAGÓGICOS DOS CURSOS DE DESIGN: O CASO DE UMA GRADUAÇÃO E DE UM CURSO TÉCNICO EM SÃO LUÍS - MA - Silva, Inez Maria Leite da (2008)
Interdisciplinary in the elaboration of Pedagogical Political Projects (PPP) in Design courses. One verifies that the curriculum structure which is organized from isolated subjects make difficult the adoption of practices which make possible the change of attitude of the ones involved, allowing the proper approach among the subjects, which is necessary for interdisciplinary implementation. One analyzes aspects relating to the integration process among the subjects from Design course at Universidade Federal do Maranhão (UFMA) in order to subsidize the elaboration of its own Pedagogical Political Project. One presents a survey about the history of design teaching since its origin, passing by its introduction in Brazil and in Maranhão as well as UFMA design course evolution until the present days. One verifies changes relating to interdisciplinary, present in the legislation concerning to Design teaching. It surveys aspects related to the subject through questionnaires which were made to teachers and students from UFMA and CEFET/MA courses. One highlights strategies and methodologies which can be adopted by teaching institutions in the sense of making an effective interdisciplinary project. The results of this research are based in considerations made by several authors: Niemeyer (1998), Freitas (1999), Dias (2004), Fazenda (1992), Alves (2000), Santomé (1998), Japiassu (1976) and others. The surveyed and analyzed data contributed to broaden knowledge about the interdisciplinary which is present in those courses, important to reinforce the construction, implementation, monitoring and subsequent evaluation of UFMA design course PPP. The interdisciplinary work depends mostly on the awareness, will and attitude of all the people which are involved in front of unchangeable procedures and conducts which are set up on the everyday teaching. It is very difficult to modify, without the proper intention, the inveterate way of teaching and learning, unless people, aware of the fact, mobilize themselves regarding this change.